Economics of Integrated Fish-Chicken Farming System (Longyam) in Tasikmalaya District, Indonesia - Kusumawardhani, Amie (1991)

(untitled)
The study is an at tempt to analyse the economic aspects of Integrated Fish - Chicken Farming System (longyam) in the District of Tasikmalaya, Indonesia. Linear Programming was employed as an analytical tool to determine the optimal enterprise-mix and allocation of resource use for three farm categories: small, medium and large. The Functional Mathematical Programming System (FMPS) was used to obtain the solution required. Primary data was collected from a farm survey and secondary data obtained from relevant agencies were used as supplementary information. The study found that large farmer searned the highes tnet prof it for all the five fish species i.e. mas, nilem, tawes, tambakan and nit as compared to small and medium farmers. Small farmers obtained the highest net profit in broilers and layers production. On the other hand, medium farmer sled in raising cockerels. It was also shown that the total costs in culturing fish as well as raising chicken a farm declined as farm size increased. The optimal solutions generated a higher total net revenue for the three farm categories over the existing practice. Large farmers have a greater potential for earning a higher income than small and medium farmers. The inclusion of chicken enterprise in the solution increased the employment of labour on small, medium and large farms in all the months of the planning period. The largest increase in labour utilisation was in small farms fol lowed by large and medium farms. Government intervention through the injection of subsidised credit to cooperative or farmers 'association can go a long way in increasing farmers' income. In addition, the role and involvement of extension workers can be intensified for better enterprise management and adopt ion of new technology in longyam.